"What are We Trying to Accomplish?": Student Resistance as Racial Wisdom. Issue 1 (2nd January 2019) - Sosa, Teresa; Latta, Mark
ABSTRACT: This work analyzes a Grade 9 English Language Arts classroom discussion for moments of resistance and asks, What does student resistance accomplish when viewed as racial wisdom? Drawing from "posts" traditions, we analyzed the discussion's intra-actions or entanglements in order to more clearly understand how students draw from their "well of knowledge" to resist. Findings indicate student resistance interrupts the grammar of schooling and, at the same time, creates new openings for other ways to disrupt and resist. This work demonstrates the importance of situating resistance as counter narratives grounded in racial wisdom that work to reconfigure interpretations and definitions of personal and social identities situated more completely within embodied experiences.